2012
DOI: 10.1111/j.2044-8287.2012.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

An interpretative phenomenological analysis of the patient experience of awake craniotomy: Brain tumour diagnosis to discharge

Abstract: Thesis AbstractIntroduction. This thesis explored patient experiences of awake craniotomy.Existing literature is scarce and dominated by quantitative methodologies. More recently two qualitative studies have provided a rich, but contrasting, understanding of the patients" experience of awake craniotomy.The methodological weaknesses of the existing literature are addressed, and the rationale for the study justified. Objectives.The aim of the study was to explore seven participants" experiences of awake cranioto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
0
15
0
2
Order By: Relevance
“…These patients further expressed that they did not just want their surgeon to be capable and confident but also to show compassion, as signs of compassion was interpreted as the neurosurgeon could be trusted and would act humanely (Rozmovits et al., ). In addition, several studies have argued of the importance of a providing a stable relationship with members of the medical staff and especially the neurosurgeon (Fletcher, Das Nair, Macniven, Basu, & Byrne, ; Philip et al., ; Rosenblum et al., ). Fletcher et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These patients further expressed that they did not just want their surgeon to be capable and confident but also to show compassion, as signs of compassion was interpreted as the neurosurgeon could be trusted and would act humanely (Rozmovits et al., ). In addition, several studies have argued of the importance of a providing a stable relationship with members of the medical staff and especially the neurosurgeon (Fletcher, Das Nair, Macniven, Basu, & Byrne, ; Philip et al., ; Rosenblum et al., ). Fletcher et al.…”
Section: Discussionmentioning
confidence: 99%
“…Fletcher et al. () found that the stable trustful relations enable patients to use self‐preservation strategies; for example, choosing to avoid information they do not feel ready to master and instead trusting the neurosurgeon completely to take over. In this way, a relationship based on trust may compensate for the lack of specific information often experienced by patients either due to the use of patients’ self‐preservation strategies, the cognitive deficits caused by the brain tumour or an impaired ability to attain information due to the overwhelming situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While care processes, at least regarding medication management, continue to appear routinised, meaningful relationships between the recipients and providers can be formed which is in contrast to the literature suggesting routines act as a deterrent to this process (McCormack, Karlsson, Dewing, & Lerdal, 2010;Wolf et al, 2012). Establishing a personal connection with the doctor in particular appears to impact the patient's emotional wellbeing, however this could be due to the existence of a unique 'awake craniotomy' patient-to-neurosurgeon relationship (Fletcher, das Nair, Macniven, Basu, & Byrne, 2012).…”
Section: Theme 3: Emotional Securitymentioning
confidence: 93%